ANALISIS KEMAMPUAN METAKOGNITIF DALAM PEMECAHAN MASALAH MATEMATIS DITINJAU DARI GAYA BELAJAR HONEY-MUMFORD - Viona Yuliza; Huda, Nizlel; Junita, Ranisa (Universitas Muhammadiyah Metro, 2024)
This study was conducted to analyze the level of metacognitive ability in mathematical problem solving in terms of Honey-Mumford learning style in class XI students. This research uses descriptive qualitative research. The results obtained in this study through test data, Think aloud, and interviews that have been conducted by the eight subjects are found that the eight subjects are able to determine the information contained in the problem given. The eight subjects were also able to develop a solution plan, even making conclusions from the given solution steps. However, all eight subjects had weaknesses in re-examining the answers, and only some of the subjects were able to correct the mistakes made. Therefore, the conclusion that can be given in this study related to the level of metacognitive abilities in mathematical problem solving in terms of Honey-Mumford's learning style is that and subjects are at the Strategic use metacognitive ability level. While and subjects are at the Reflective use metacognitive ability level.